Do Dynamic Provisions Enhance Bank Solvency and Reduce Credit Procyclicality? : a Study of the Chilean Banking System - Chan-Lau, Jorge (IMF Working Papers; Working Paper, 2012)
Dynamic provisions could help to enhance the solvency of individual banks and reduce procyclicality. Accomplishing these objectives depends on country-specific features of the banking system, business practices, and the calibration of the dynamic provisions scheme. In the case of Chile, a simulation analysis suggests Spanish dynamic provisions would improve banks' resilience to adverse shocks but would not reduce procyclicality. To address the latter, other countercyclical measures should be considered.